Nutrition status screening and assessment in colorectal cancer patients - Liu Hong; Lin Xiaoqian; Yang Jian (结直肠肛门外科)
Colorectal cancer is a common gastrointestinal malignancy in China and worldwide. Patients with colorectal cancer are at risk of compromised nutritional status or malnutrition. The nutritional status of these patients is closely linked to patients’ treatment tolerance, quality of life, and prognosis. Standardized nutritional diagnosis and treatment is multifaceted, including nutrition status screening, assessment, intervention (treatment), and monitoring. Nutrition status screening and assessment are the most critical steps of nutritional diagnosis and treatment, but also the basis and premise of intervention (treatment). In this article, we present a comprehensive overview of the state-of-the-art nutrition status screening and assessment of patients with colorectal cancer, aiming to provide valuable insight into these patients’nutrition diagnosis and intervention.